Hidrolases de fungos isolados da Mata Atlântica cultivados em resíduos agroindustriais: Produção, Purificação e Caracterização Enzimática - Andrades, Diandra de (2014)
In recent years the use of biotechnological processes with microorganisms has been highlighted, in particular the production of enzymes and commercial market. The objective of this study was to investigate the potential six filamentous fungi (Aspergillus aculeatus, Aspergillus fumigatus, sitophila Chrysonilia, Gliocadium virens, Aspergillus flavus and Trichoderma longibrachiatum isolated from Atlantic West of Paraná and its ability to produce hydrolytic enzymes of the cellulolytic complex, xylanolytic, pectinase and disaccharidases (β-galactosidase, β-glucosidase and β-fructofuranosidase), as well as purify and characterize the β-fructofuranosidase from A. flavus. The fungus A. aculeatus exhibited great potential in the production of intracellular β-galactosidase (56,31 U/ml) with orange peel as substrate, intracellular β-fructofuranosidase (409.46 U/mL) with the trub (brewing residue) and intracellular β-glucosidase obtained with passion fruit peel (192.2 U/ml). C. sitophila showed increased production of intracellular β-galactosidase with sorghum straw (16.48 U/ml) and intracellular β- xylosidase with orange peel (4.60 U/ml). A. fumigatus also was a good producer of β- galactosidase intracellular (17.26 U/ml) with passion fruit peel and extracellular pectinase (45.95 U/ml) with orange peel. However, Gliocadium virens produced only intracellular β-galactosidase (22.57 U/ml) with rice straw. While T. longibracitum exhibited the best enzymatic production of enzymes xylanase (22.38 U/ml) with sorghum straw; pectinase (26.43 U/ml) with orange peel and intracellular betagalactosidase (17.53 U/ml) using passion fruit peel. In addition, Aspergillus flavus achieved excellent levels β-fructofuranosidase both in liquid culture and in solid culture when supplemented with soybean meal or trub, but the enzymatic production of solid cultivation was 5 times higher than the liquid culture. Thus, beta-fructofuranosidase obtained under solid state cultivation of soybean meal was partially purified with 19% overall yield with an apparent molecular mass of 37 kDa by SDS-PAGE and 45 kDa in native form. The pH and the optimum temperature for enzyme activity were 5.0 and 60°C, respectively. The enzyme was stable at 70% residual activity after 12 hours in the acid pH range (5.0 to 5.5), while at temperatures of 45°C to 55°C the enzyme showed higher stability than 50%